2018
DOI: 10.1186/s12936-018-2566-0
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the IgG antibody response to Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, and Plasmodium ovale MSP119 subunit proteins in multiplexed serologic assays

Abstract: BackgroundMultiplex bead assays (MBA) that measure IgG antibodies to the carboxy-terminal 19-kDa sub-unit of the merozoite surface protein 1 (MSP119) are currently used to determine malaria seroprevalence in human populations living in areas with both stable and unstable transmission. However, the species specificities of the IgG antibody responses to the malaria MSP119 antigens have not been extensively characterized using MBA.MethodsRecombinant Plasmodium falciparum (3D7), Plasmodium malariae (China I), Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 82 publications
8
56
1
1
Order By: Relevance
“…Rates of non-falciparum malaria are thought to be low in Mozambique, but there are limited data. However, serological studies have shown rates of antibody seropositivity ranging from 35% to 56% to Plasmodium malariae and P. ovale in the north of the country (5,6). A previous study reported a single Pfhrp2-deleted parasite from Mozambique, found among 1,162 samples collected from a single site in the south of the country (7).…”
mentioning
confidence: 99%
“…Rates of non-falciparum malaria are thought to be low in Mozambique, but there are limited data. However, serological studies have shown rates of antibody seropositivity ranging from 35% to 56% to Plasmodium malariae and P. ovale in the north of the country (5,6). A previous study reported a single Pfhrp2-deleted parasite from Mozambique, found among 1,162 samples collected from a single site in the south of the country (7).…”
mentioning
confidence: 99%
“…Far lower frequencies of cross-reactivity were observed in other studies. Using a multiplex bead assay, the species specificity of IgG responses to the MSP1 19 region from P. falciparum, P. ovale, P. vivax, and P. malariae was evaluated in sera from experimentally infected chimpanzees, infected individuals living in low transmission settings in Haiti and Cambodia (n = 12), and sera eluted from blood spots collected from individuals living in a high transmission setting in Mozambique (n = 20) (70). All of the antibody responses from the chimpanzees were speciesspecific and recognition was completely blocked by competition with the homologous protein.…”
Section: Erythrocytic Targetsmentioning
confidence: 99%
“…Six Plasmodium antigens were used for IgG antibody detection: the species-specific merozoite surface protein 19kD (MSP1) fragments for P. falciparum, P. vivax, and P. malariae (as described previously [8]), and three other P. falciparum antigens: liver stage antigen 1 (LSA1, [20]), circumsporozoite protein (CSP, NANPx5 repeat, [20]), and glutamate-rich protein R0 fragment (GLURP-R0, [21]). The three Plasmodium MSP1 19 kD antigens were produced recombinantly and purified as described previously [8], and the three other P. falciparum antigens were produced as peptides. The Schistosoma japonicum glutathione-S-transferase antigen was produced recombinantly and served as a generic protein to assess IgG non-specific binding.…”
Section: Blood Elution and Multiplex Bead Assaysmentioning
confidence: 99%
“…Individuals with high levels of parasite-specific antibodies lower susceptibility to Plasmodium falciparum infection and morbidity [6]. The Plasmodium merozoite surface protein 1 (MSP1) antigen has been well characterized in immunological studies, and is known to induce "long-lived" IgG responses [7], with species-specific isoforms eliciting specific responses with limited cross-reactivity [8]. Plasmodium exposure even at a young age has the potential to induce a decades-long, or even life-long, antibody response.…”
Section: Introductionmentioning
confidence: 99%